Investigating the effectiveness of an intraoperative decision support guided fluid therapy intervention on postoperative outcome of high-risk patients undergoing high-risk abdominal surgery: protocol for an international multicentre stepped-wedge cluster-randomised implementation trial - Sean Coeckelenbergh; Amelie Delaporte; Damien Rousseleau; Jacques De Montblanc; Stephanie Roullet; Joanna Ramadan; Bernard Cholley; Alexandre Stibon; Emmanuel Weiss; Maria-Christina Kassab; Sylvain Diop; Elsa Manzi; et al. (BJA Open)
Background: Inappropriate fluid administration can impact patient outcome. Intraoperative advanced haemodynamic monitoring coupled with a treatment protocol based on stroke volume optimisation can help determine the appropriate timing for fluid boluses. Although recommended by several anaesthesia societies, this strategy is rarely implemented because protocols are complex and compliance is often poor. The Acumen Assisted Fluid Management (AFM) software is a decision support system that uses machine learning to predict fluid responsiveness and individualise fluid therapy. AFM reportedly predicts fluid responsiveness better than clinicians, decreases preload-dependent states, and improves both macro- and microcirculatory variables. The goal of this international multicentre stepped-wedge cluster randomised trial is to test whether implementing AFM during high-risk surgery improves patient outcome. Methods: The trial is ongoing in 16 academic hospitals in France, Belgium, Canada, and the USA. All centres (clusters) deliver routine care (control arm) at the start of the study and crossed over (one way) to AFM-guided fluid therapy (intervention arm). The time when different centres switch to AFM is randomised by an independent statistician. At the end of the trial, all centres will cross over to the intervention group. The primary outcome is a composite of major complications and death 30 days after surgery that will be analysed as intention-to-treat. A total of 2000 patients are required to detect a relative 20% differences in the primary outcome between groups. Conclusions: This trial is powered to provide evidence on whether implementing AFM is effective in reducing postoperative complications in high-risk patients after high-risk abdominal surgery. Clinical trial registration: NCT06011187.